Risk Factors for Fragility Hip Fracture in the Older in Northern Thailand: A Community-Based Retrospective Cohort Study - Waiwattana, Krairoek; Sucharitpongpan, Worapong; Daraphongsataporn, Nuttorn (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: This community-based retrospective cohort study aimed to identify risk factors for fragility hip fractures among older individuals in three districts of Nan Province, Thailand. The study addresses a knowledge gap regarding hip fracture risk factors specific to northern Thai communities. Methods: Health data from the Nan Provincial Health Office database, covering the period January 1, 2019 to December 31, 2023, were analyzed for 36,521 older individuals aged ≥ 60 years. Participants had no prior history of hip fracture. Data on demographics, chronic diseases, use of walking aids, history of non-hip fragility fractures, and FRAX hip scores were collected. Multivariate Cox regression analysis was performed to identify significant risk factors for hip fractures. Results: Key risk factors for hip fractures included female sex, age ≥ 70 years, body mass index (BMI) < 20 kg/m², use of walking aids, history of non-hip fragility fractures, hypertension, chronic obstructive pulmonary disease (COPD), chronic kidney disease, cerebrovascular accident, and Parkinson’s disease. In males, significant risk factors included a BMI < 20 kg/m² and COPD, whereas in females, risk factors included hypertension, use of walking aids, and a FRAX hip score > 3.3%. Diabetes mellitus, dementia, heart disease, and lack of a caregiver were not found to be significant risk factors. Conclusions: This study identified key risk factors for fragility hip fractures among community-dwelling older individuals in Northern Thailand, highlighting sex-specific risk profiles. The findings emphasize the need for targeted prevention strategies. Additionally, certain risk factors may be influenced by regional characteristics, geographical factors, and cultural aspects, limiting their generalizability.